2002
DOI: 10.2166/wst.2002.0273
|View full text |Cite
|
Sign up to set email alerts
|

Application of locally available materials for the treatment of organic polluted water

Abstract: Several types of water treatment technologies including adsorption are now being used to treat polluted water. In this paper the removal of phenol by adsorption will be discussed. Activated carbons are successfully applied for purification of potable water and the removal of organic pollutants in wastwater. This paper is concerned with a low cost approach to treating waste water that is significant especially for those countries where oil palm is an available agricultural product like Malaysia, Ivory Coast, Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Solar photo-catalytic oxidation, which is influenced by both the number of active sites and the penetration of irradiation light, must therefore pass through a maximum at optimum catalyst loading. Also, the decrease in adsorption density with increase in adsorbent amount is due to the high number of unsaturated adsorption sites [46][47][48][49]. It should also be noted that the optimum value of catalyst loading is strongly dependent on the type and initial concentration of oil and the operating conditions of the solar photo-reactor [46][47][48][49][50].…”
Section: Effect Of Catalyst Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Solar photo-catalytic oxidation, which is influenced by both the number of active sites and the penetration of irradiation light, must therefore pass through a maximum at optimum catalyst loading. Also, the decrease in adsorption density with increase in adsorbent amount is due to the high number of unsaturated adsorption sites [46][47][48][49]. It should also be noted that the optimum value of catalyst loading is strongly dependent on the type and initial concentration of oil and the operating conditions of the solar photo-reactor [46][47][48][49][50].…”
Section: Effect Of Catalyst Dosementioning
confidence: 99%
“…Also, the decrease in adsorption density with increase in adsorbent amount is due to the high number of unsaturated adsorption sites [46][47][48][49]. It should also be noted that the optimum value of catalyst loading is strongly dependent on the type and initial concentration of oil and the operating conditions of the solar photo-reactor [46][47][48][49][50]. In our study, the optimum catalyst loadings of TiO2NFs is 0.5 g/l.…”
Section: Effect Of Catalyst Dosementioning
confidence: 99%
“…5, which demonstrates that the COD concentration in the effluent complies with standard A of Malaysia's regulations for wastewater (50 ppm) [19] for the first 80 min of breakthrough time. The efficiency of the column could also be calculated by using Equation (3) as suggested by Eckenfelder [16,23]: where E is the column efficiency, H is the column height and H c is the critical column height (obtained from the Bohart-Adam equation at t = 0). Leachates contain large amounts of organic contaminants which can be measured as chemical oxygen demand (COD) and biological oxygen demand (BOD), ammoniacal nitrogen, halogenated hydrocarbons, and suspended solid, significant concentration of heavy metals and inorganic salts [2,3].…”
Section: Fixed Bed Adsorption Studymentioning
confidence: 99%
“…It is only in recent years the interest to palm shell has increased, mainly due to the research findings that this material can be an excellent source of high quality and low cost activated carbon. However, most of the studies on palm shell activated carbon (PSAC) are focused on the parameters of the activation/carbonization procedures [3][4][5][6][7][8][9] and so far only few examined the adsorption capacity of this material [10][11][12]. A recent study conducted by our research team [13] showed that palm shell activated carbon has high capacity to adsorb lead ions compared to other types of activated carbons.…”
Section: Introductionmentioning
confidence: 99%